Circulating tumor cells detection has independent prognostic impact in high‐risk non‐muscle invasive bladder cancer. Issue 8 (13th March 2014) - Gazzaniga, Paola; de Berardinis, Ettore; Raimondi, Cristina; Gradilone, Angela; Busetto, Gian Maria; De Falco, Elena; Nicolazzo, Chiara; Giovannone, Riccardo; Gentile, Vincenzo; Cortesi, Enrico; Pantel, Klaus
<x xml:space="preserve">Abstract</x> High‐risk non‐muscle invasive bladder cancer (NMIBC) progresses to metastatic disease in 10–15% of cases, suggesting that micrometastases may be present at first diagnosis. The prediction of risks of progression relies upon EORTC scoring systems, based on clinical and pathological parameters, which do not accurately identify which patients will progress. Aim of the study was to investigate whether the presence of CTC may improve prognostication in a large population of patients with Stage I bladder cancer who were all candidate to conservative surgery. A prospective single center trial was designed to correlate the presence of CTC to local recurrence and progression of disease in high‐risk T1G3 bladder cancer. One hundred two patients were found eligible, all candidate to transurethral resection of the tumor followed by endovesical adjuvant immunotherapy with BCG. Median follow‐up was 24.3 months (minimum–maximum: 4–36). The FDA‐approved CellSearch System was used to enumerate CTC. Kaplan–Meier methods, log‐rank test and multivariable Cox proportional hazard analysis was applied to establish the association of circulating tumor cells with time to first recurrence (TFR) and progression‐free survival. CTC were detected in 20% of patients and predicted both decreased TFR (log‐rank p < 0.001; multivariable adjusted hazard ratio [HR] 2.92 [95% confidence interval: 1.38–6.18], p = 0.005), and time to progression (log‐rank p < 0.001; HR 7.17 [1.89–27.21], p = 0.004). The present findings provide evidence that CTC analyses can identify patients with Stage I bladder cancer who have already a systemic disease at diagnosis and might, therefore, potentially benefit from systemic treatment.